Blocking α5β1 Integrin Attenuates sCD40L-Mediated Platelet Activation. (September 2017) - Simic, Damir; Bogdan, Nancy; Teng, Fang; Otieno, Monicah
The soluble form of CD40L (sCD40L) is a platelet-derived mediator that links inflammation, hemostasis, and vascular dysfunction. Indeed, blockade of CD40L by neutralizing antibodies or genetic disruption in mice prevents atherosclerosis and atherothrombosis. Until recently, it was believed that CD40 and αIIbβ3 were the only receptors on platelets responsible for binding sCD40L, leading to platelet activation and initiation of thrombotic events. Recent findings showed α5β1 integrin as a novel platelet sCD40L receptor, with an unknown function. For the first time, using anti-α5β1 blocking antibodies, we show that sCD40L/α5β1 interaction leads to platelet activation as evaluated in the human whole blood. Establishing α5β1 integrin's role in platelet activation, and therefore thrombosis will help further shed light on the etiology of thrombotic disease.